AN EFFECTIVE LOST AND FOUND SYSTEM IN UNIVERSITY CAMPUS - Siok Yee Tan; Cia Rui Chong, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Different organizations and researchers have carried out much work to highlight the problem of lost and misplaced items. In this work, a web and mobile-based lost and found service for The National University of Malaysia (UKM) is designed and developed. The primary goal of this research is to help the students, staff, and visitors on the UKM campus find their lost items more efficiently. The main features of this web and mobile application included a login system and a lost and found listing page where the user can add things they have discovered or items reported as lost. Users can add extra information about the items, such as where the items are found or lost, and even attach pictures. Besides, users must update their contact information and matric number to ensure authenticity. Due to security issues, users must add security questions for every post to protect users from any frauds and tricks. Once the users have held an item for over a month, the disposal system will automatically delete the item. The application is an online lost and found system created using programming languages such as PHP, HTML, CSS, and Java Script connected to the MySQL database. The software used in this project is Sublime Text, XAMPP, and Filezilla, whereas the software used to develop the mobile application is Android Studio, and the programming language is Java. In conclusion, the system has successfully helped the students and staff of UKM to find their lost belongings and items faster and easier. This research also played an essential role in creating an efficient digital campus environment and enhancing the university's sustainability.